Assessing residents' flood preparedness through adaption of protective behaviour in Melaka, Malaysia - Sufian, Atirah; Chai, Jia Chi; Azman, Hartini; Fam, Soo Fen; Abdul Aziz, Nor Azah; Mohd Zamri, Ammar Afif (Horizon Research Publishing, 2022)
Flood is a natural disaster experienced by Malaysians including residents in Melaka. Floods cause huge damage and loss, and can affect the health of the flood victims. However, flood prone residents’ awareness and preparation towards floods are still lacking. Despite many efforts done by different organizations to reduce the flood risk, flood hazard remains the main problem in Melaka. Several studies had been conducted to investigate the level of flood preparedness in some regions in Malaysia, but the level of flood preparedness amongst residents in Melaka is still unknown. Therefore, this research is conducted to assess the Melaka residents’ flood preparedness using the Adoption of Protective Behaviour (APB) scale. The nine measurements APM scale is utilized and another three measurement items are created and added into the scale which makes it twelve measurement items. The mean for the twelve measurement items ranges between 2.85 to 4.03 while the likelihood percentage ranges between 31.67% and 74.17%. The twelve measurement items are significantly correlated with flood preparedness of the residents in Melaka. The result shows that flood preparedness among the residents in Melaka is still low. Most respondents are not well prepared in facing the flood. As the study was conducted on the states of Melaka only, it is recommended that future study should be carried out in all states in Malaysia especially in the east coast of Malaysia where large scale flooding occurs every year. The findings in this research can assist the authorities and the government to plan on creating public awareness and education for flood disasters. This helps the residents in Melaka to increase their knowledge on flood risk and establish an emergency plan for their families. The study also shows that residents in flood prone area put inadequate efforts in preparing for a flood event.